2015
DOI: 10.4236/as.2015.61016
|View full text |Cite
|
Sign up to set email alerts
|

Humic and Oxalic Acid Stimulates Grain Yield and Induces Accumulation of Plastidial Carbohydrate Metabolism Enzymes in Wheat Grown under Sandy Soil Conditions

Abstract: Humic and oxalic acids have the effects of promoting plant growth. We test whether they are able to positively impact wheat yield under newly reclaimed sandy soil, where water deficiency negatively influences yield. Foliar application of humic acid and oxalic acid on two wheat cultivars, Gemiza-9 and Sakha-93, leads to overall better performance of the plants and increases the yield significantly, irrespective of the cultivar genetic background. However, Gemiza-9 surpassed Sakha-93 in grain yield parameters. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 26 publications
3
14
0
Order By: Relevance
“…ions uptake and transport, , transpiration, photosynthesis, growth and plant metabolism. These findings are in partial well-matched with those recorded by Rood et al (1990), Malencic et al (2004), Chauhan et al (2009), Singh et al (2010, Ghodrat et al (2012), Babakhaani et al (2013), El-Shabrawi et al (2015) and Mustafa and Awang Soh (2016). Plant height (cm), ear height (cm), ear leaf area (cm 2 ), number of ears/plant, ear length, (cm)…”
Section: Effect Of Growth Promoter Substancessupporting
confidence: 89%
See 1 more Smart Citation
“…ions uptake and transport, , transpiration, photosynthesis, growth and plant metabolism. These findings are in partial well-matched with those recorded by Rood et al (1990), Malencic et al (2004), Chauhan et al (2009), Singh et al (2010, Ghodrat et al (2012), Babakhaani et al (2013), El-Shabrawi et al (2015) and Mustafa and Awang Soh (2016). Plant height (cm), ear height (cm), ear leaf area (cm 2 ), number of ears/plant, ear length, (cm)…”
Section: Effect Of Growth Promoter Substancessupporting
confidence: 89%
“…Moreover, adding has received much attention in relation to, induced disease systemic resistance and its antioxidant capability (Malencic et al, 2004). El-Shabrawi et al (2015) indicated that foliar application with oxalic acid indicated significant increments in growth of plant, maize yield and its components.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a great deal of attention has been directed toward increasing wheat productivity per unit land, especially in newly reclaimed soils, to minimize the gap between Egyptian production and consumption (Amal et al 2011). El-Shabrawi et al (2015 revealed that the wheat yield per unit area could be increased by breeding high yielding varieties, applying optimum cultural practices and employing agronomic practices that sustain soil fertility through their effect on the physical, chemical, and biological properties of the soil.…”
Section: Problem and Solution Statementmentioning
confidence: 99%
“…It has been known to be one of the important cereal crops providing 37% of total calories to humans and 40% of the protein in our diet [11]. It was also found that wheat yield per unit area can be increased if we use high yielding wheat varieties, improved agriculture practices, genetically improved or modified wheat germplasm and improved agronomic practices [12]. Therefore, the present is study is conducted to find out the correlation of AM fungi spores and root colonization with the soil characteristics of wheat (Triticum asativam L.).…”
Section: Introductionmentioning
confidence: 99%